A hybrid model predictive charging control strategy for ultracapacitors of urban rail vehicles - Yuanjun Chen; Xiaoyong Zhang; Zhiwu Huang; Jun Peng; Zheng Xu; Yanhui Zhou (2016 IEEE Energy Conversion Congress and Exposition (ECCE), 2016)
Ultracapacitors have been widely used in urban rail vehicles as the power source because of its high power density. However, it is still a challenge to design a rapid and reliable charging control system for ultracapacitors since the DC-DC converters are highly nonlinear along with hard constraints. In this paper, the piecewise-affine (PWA) model of the ultra-capacitor charging system and a hybrid model predictive control strategy are proposed to address this challenge. The hybrid nature of the converter is taken into account in v-resolution model which can reflect the dynamics of the charging system precisely. Based on the discrete-time model, we formulate and solve a constrained optimal control problem, and the control law is calculated offline using multi-parameter programming method. Simulation and experiment results validate the potential advantages of the proposed scheme.